A pharmacokinetic study of morphine‐6‐O‐sulfate in rat plasma and brain. Issue 6 (11th January 2021) - Yadlapalli, Jai Shankar K.; Albayati, Zaineb A. F.; Breen, Philip J.; Dobretsov, Maxim; Penthala, Narsimha R.; Hendrickson, Howard P.; Crooks, Peter A.
Abstract: Morphine‐6‐ O ‐sulfate (M6S), a polar, zwitterionic sulfate ester of morphine, is a powerful and safe analgesic in several rat models of pain. A sensitive liquid chromatography–tandem mass spectrometry bioanalytical method was developed and validated for the simultaneous determination of M6S and morphine (MOR) in rat plasma and brain after M6S administration. Morphine‐d6 was used as internal standard. Multiple reaction monitoring was used for detection and quantitation of M6S, MOR, and morphine‐d6 in the turbo ion spray positive mode. The chromatographic separation was carried out on an Alltech Altima C18 column. The analytical method was validated for linearity, precision, accuracy, specificity, and stability over a concentration range of 3–8000 ng/ml in rat plasma and 10–10, 000 ng/ml in brain samples for both M6S and MOR. The validated method was applied to determine the PK profile of M6S in plasma after i.v., i.p., and oral dosing in male Sprague–Dawley rats. Rats were administered M6S by i.p. administration (5.6 and 10.0 mg/kg) or orally (10 and 30 mg/kg) and bioavailability compared to an i.v. injection (1 mg/kg) of M6S. The in vivo results indicate that M6S is not a prodrug of morphine, since M6S is not biotransformed into MOR in plasma after either i.p. or oral administration, and MOR was not detected in brain. The bioavailability of M6S was >93% and about 5% after i.p. and oral dosing, respectively. The low oral bioavailability of M6S may be due to poor permeation of the intestinal epithelial membrane. After i.p.‐administration, M6S appears to reach brain tissues in low, but significant, concentrations.